Breast tumors in females: A Review Of 500 Malignant Cases. - Talal, Lubab F. (Journal of the Faculty of Medicine Baghdad, 2009)
Background:Breast carcinoma is the most common malignant tumor and the leading cause of carcinoma death in women, with more than 1,000,000 cases occurring worldwide annually.(1) as a matter of fact , the mortality rate for breast carcinoma changed very little from the 1930s to the early 1990s, because of the combined action of earlier diagnosis and improved therapy . Materials and methods: The prospective study included 500 cases of breast carcinoma who went total mastectomy , between October 2006- April 2007, where taken from private pathology laboratory , sections(4microns) are taken and stained with H&E stain and over-reviewed. Results: Clinicopathological analysis of the 500 cases of breast carcinoma, including the age, clinical presentation, the site of the tumor, the mammography results, the microscopic morphology, the stage and the grade of the tumor. The age in relation to the morphological classification also analyzed. Conclusion: The commonest breast carcinoma in women is invasive ductal carcinoma, followed by lobular carcinoma, with mean age 44.5 year, mainly in the left breast, and that mammography approach is so useful in early detection of breast carcinoma.